THE EFFECT OF BRAIN GYM ON STRESS LEVELS IN STUDENTS OF AL-HASYIMIYYAH ISLAMIC MIDDLE SCHOOL - Putri Luvi kurniawati; Lailatul Fadilah; Osep Yasier Almunsiri (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Background : Stress is a natural response of the body and mind to pressure or change that requires adjustment. Continuous stress and depression can have a negative impact on the mind and can also weaken the immune system. The most common stress experienced by students in school is academic stress. Academic stress has a negative impact on physical health. One of the academic stressors is stress related to adolescent learning activities at school. Brain Gym is a program designed to improve several aspects of an individual's cognitive and psychological well-being. Brain gym is done through a series of simple movement exercises that test the two sides of the brain, namely the left brain and the right brain. Doing brain gym is one way to relieve stress. Objective : To determine the effect of brain gym on stress levels in students during learning at school. Method : This study used a quasi-experimental research design with the One Group Pretest-Posttest Design approach, this study did not involve a control group. The sampling of this study used a nonprobability sampling technique, namely purposive sampling with a total of 26 respondents. Results : the results of the univariate test obtained an average value of stress levels before being given brain gym was 25.38 and the bivariate test using the T-test obtained a P value of .000. Conclusion : There is an effect of brain gym on reducing stress levels in students of Al-Hasyimiyyah Islamic Middle School.